Egg quality of laying hens fed diets with plant extracts - Moraleco, Debora Duarte; Valentim, Jean kaique; Silva, Larissa Gonçalves; Lima, Heder José D’Ávila; Bitencourtt, Tatiana Marques; Dallago, Gabriel Machado (Acta Scientiarum. Animal Sciences, 2019)
The objective of this study was to evaluate the effect of marigold flower extract and paprika on egg quality of Black Avifran laying hens in different periods of storage. A completely randomized design study with a 3x3 factorial scheme with three diets (control, paprika, and marigold flower extract) and three storage periods (0, 7, and 14 days) was carried out. The following metrics were evaluated: egg weight, yolk weight, shell weight; yolk color, albumen height, specific gravity, and Haugh unit as well as the yolk, shell, and albumen percentage relative to the total weight of the egg. There was no significant interaction between additives and storage time (p > 0.05) for most of the parameters evaluated. The only exception was observed for yolk color, in which the interaction effect between treatments was significant (p < 0.05). The effect of storage time was significant (p < 0.05) for albumen weight, albumen percentage, yolk color, albumen height, specific gravity, and Haugh unit, with reduction of these parameters over the evaluation period. The use of paprika and marigold flower extract in the diets of Black Avifran laying hens does not influence egg quality.